Pancreatic heterotopia as a cause of dyspepsia - Tonkin, R. D. (1962)
Four cases of pancreatic heterotopia are reported. It is considered that this pathology may cause severe, persistent dyspepsia and may escape detection at laparotomy unless the stomach is opened.